Navigating The Digital Marketplace: A Qualitative Study Of Digital Consumer Behavior In The Era Of Social Media, AI, And Mobile Commerce - Hery Maulana Arif (International Humanity Advance, Business & Sciences, 2026)
Digital consumer behavior has become increasingly complex due to the rapid integration of social media, artificial intelligence (AI), digital payment systems, and mobile commerce into everyday consumption practices. While prior studies have predominantly relied on quantitative approaches and behavioral analytics, limited research has explored how consumers subjectively interpret and navigate these interconnected digital environments. Addressing this gap, this study investigates consumers’ lived experiences and perceptions regarding digital footprints, influencer marketing, AI-driven personalization, digital payments, and mobile commerce. Using an interpretive qualitative design, data were collected through semi-structured in-depth interviews with 20 purposively selected participants from diverse demographic backgrounds. The data were analyzed using thematic analysis. The findings reveal five major themes: (1) awareness of digital footprints accompanied by privacy tensions, (2) the central role of social media influencers and perceived authenticity in shaping purchase intentions, (3) the convenience–surveillance paradox of AI-driven personalization, (4) trust and generational differences in digital payment adoption, and (5) the dominance of smartphones as the primary interface for mobile commerce. The study demonstrates that digital consumers are neither passive recipients of marketing technologies nor fully rational decision-makers; instead, their engagement is mediated by trust, convenience, authenticity, and perceived transparency. This research contributes to the qualitative consumer behavior literature by providing a richer understanding of consumer experiences in digital marketplaces and offers practical implications for marketers, platform designers, and policymakers seeking to build more transparent, trustworthy, and consumer-centered digital ecosystems.